Hormone replacement therapy, menopausal age and lifestyle variables are associated with better cognitive performance at follow-up but not cognition over time in older-adult women irrespective of APOE4 carrier status and co-morbidities - Watermeyer, Tamlyn J.; Gregory, Sarah; Leetham, Emmi; Udeh-Momoh, Chinedu T.; Muniz-Terrera, Graciela (Frontiers in Dementia, 2025)
IntroductionThe impact of Hormone Replacement Therapy (HRT) on cognitive function in postmenopausal women remains a topic of considerable debate. Although estrogen's neuroprotective effects suggest potential cognitive benefits, empirical findings are mixed.MethodsThis study uses data from the Cognitive Function and Ageing Study Wales (CFAS Wales) cohort to explore the relationships between HRT use, age at menopause, APOE4 carrier status, lifestyle factors, comorbidities, and cognitive outcomes in older adult women. Two regression models were employed: one analyzing cognitive performance at follow-up and another examining changes in cognitive scores over time.ResultsResults indicate that while age, education, HRT use, age at menopause, alcohol consumption, and diet were associated with cognitive function at a single later time point, only age remained a significant predictor when modeling cognition over time.DiscussionThese findings suggest that while HRT, menopausal age and lifestyle factors may support cognitive stability, they do not necessarily predict cognitive decline in post-menopausal older women. A major limitation of the current work is the lack of detail regarding HRT use, such as formulation, timing and duration; caveats that future studies should address. The study underscores the need for longer follow-up periods, consideration of other female-specific risk factors, and more comprehensive lifestyle and health assessments to clarify the complex interplay between HRT use, reproductive history, lifestyle, comorbidities and cognitive aging in women.